Health Insurance Coverage and Risky Health Behaviors Among Young Adults - Baris K. Yörük (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates the relationship between health insurance coverage and risky health behaviors among young adults using the confidential version of the National Longitudinal Survey of Youth, 1997 Cohort (NLSY97). Before the Affordable Care Act required all employers to provide health insurance to employees' children until the age of 26 (before September, 2010), many health insurance contracts covered dependents through age 19. Using a regression discontinuity design framework, I find that approximately 6 percent of young adults lose their health insurance coverage once they turn 19. I also find some evidence that the discrete change in health insurance coverage status at age 19 has spillover effects on heavy drinking, especially for males, but does not have any significant impact on smoking or marijuana use habits of young adults. These results are robust under several different parametric and non-parametric models and not sensitive to the selection of samples based on gender.
Keywords: I12; I13; I18; 330; alcohol consumption; health insurance coverage; marijuana use; smoking